Upaya Meningkatkan Kemampuan Motorik Halus Anak melalui Kegiatan Menggunting dan Menempel Gambar pada Anak Kelompok A TK ABA Suwatu - Fatimah, Siti (Didaktika, 2022)
Children's fine motor skills are very important to develop and games can be an alternative. Aisyiyah Bustanul Athfal Suwatu Kindergarten also needs development because there are still some students who have not developed their fine motor skills optimally. The purpose of this learning improvement is to improve children's fine motor skills through cutting and pasting pictures. This research is in the form of collaborative class action research with actions in the form of cutting and pasting activities. This learning improvement took place at Aisyiyah Bustanul Athfal Suwatu Kindergarten, which was held in April 2019. The research subjects were students of Aisyiyah Bustanul Athfal Suwatu Kindergarten Group A, where there were 30 students, 20 boys, and 10 girls. Learning improvement activities were carried out in 2 cycles. Data collection techniques used observation and documentation, while technical data analysis used data tabulation. The results achieved in cycle 1 were not maximized so to achieve the indicators that had been determined, the improvement activities were continued in cycle 2. And in the learning improvement activities in cycle 2, the results achieved were very good, as expected and the indicators that had been determined. Based on the results of the research and discussion, it can be concluded that children's fine motor skills can be improved through cutting and pasting pictures.